Pendampingan Guru Kawasan Ekonomi Khusus (Kek) Mandalika Lombok untuk Menumbuhkan dan Mengembangkan Agensi Pembelajar yang Regulatif (Self-Regulated) Mendukung Pengembangan Sektor Industri Kreatif - Farmasari, Santi; Indriani, Eni; Wadi, Hairil (Universitas Mataram, 2024)
The Community Service Program (PKM) seeks to support educators in the Mandalika Creative Economy Zone (KEK), Central Lombok, West Nusa Tenggara (NTB) Province, in fostering and enhancing their students' agency. Learning Agency refers to the regulatory ability of individual students to plan, take actions (self-initiation), and govern their own capabilities (self-regulation) to engage more actively in society or their community. This PKM is executed in multiple phases: socialisation, preparation, training, mentoring, and evaluation. This PKM was conducted in SMKN 1 Janapria, Central Lombok Regency, with 27 teachers from several disciplines. The outcomes of this PKM indicate an enhancement in educators' comprehension of regulatory learning bodies and their capacity to formulate action plans aimed at developing student bodies, particularly for participation in the Mandalika KEK.